2020
DOI: 10.1002/ente.201901323
|View full text |Cite
|
Sign up to set email alerts
|

Studies on One‐Step‐Synthesized Hydrated Vanadium Pentoxide for Efficient Hole Transport in Organic Photovoltaics

Abstract: Recently, the use of nonfullerene acceptors (NFA) and high‐mobility less corrosive hole transport materials in organic photovoltaics (OPV) has led to the power conversion efficiency (PCE) values ≈15% for single‐junction and ≈18% for tandem‐junction cells. Herein, the development of hydrated vanadium pentoxide (HVO) films with excellent hole transport/electron blocking capabilities via a facile synthetic route with low environmental footprint is reported. Polymer solar cells (PSC) are fabricated with both stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Vishnumurthy et al reported that V 2 O 5 HTL optimized the efficiency of thienothiophene-diketopyrrolopyrole-based OSCs by up to 1.02% [ 158 ]. Remya et al prepared an efficient hole-transport/electron-blocking hydrated vanadium oxide (HVO) from V 2 O 5 powder with hydrogen peroxide [ 159 ]. In the P3HT:PC 61 BM and PBDTT-FTTE:PC 71 BM BHJ cells, HVO HTL performance was superior to PEDOT:PSS, obtaining 56% enhancement (7.12–11.14%) in the PCE for the PBDTT-FTTE:PC 71 BM-based inverted OSC with a lower degradation of 1.4% over 20 weeks.…”
Section: Hole-transporting Materials As Htls In Oscsmentioning
confidence: 99%
“…Vishnumurthy et al reported that V 2 O 5 HTL optimized the efficiency of thienothiophene-diketopyrrolopyrole-based OSCs by up to 1.02% [ 158 ]. Remya et al prepared an efficient hole-transport/electron-blocking hydrated vanadium oxide (HVO) from V 2 O 5 powder with hydrogen peroxide [ 159 ]. In the P3HT:PC 61 BM and PBDTT-FTTE:PC 71 BM BHJ cells, HVO HTL performance was superior to PEDOT:PSS, obtaining 56% enhancement (7.12–11.14%) in the PCE for the PBDTT-FTTE:PC 71 BM-based inverted OSC with a lower degradation of 1.4% over 20 weeks.…”
Section: Hole-transporting Materials As Htls In Oscsmentioning
confidence: 99%
“…The correlation of the above results provides evidence of the hydrated nature of the material. A shift was measured in the CV curve of HVO compared to bare V 2 O 5 , and this might be due to the interaction of the redox process of V 2 O 5 and the presence of water molecules; the curve is shown in Figure S2b. The calculated HOMO energy level for HVO was 5.10 eV; the lowest unoccupied molecular orbital (LUMO) could also be measured by the addition of the optical band gap ( E opt g ) obtained from the UV–vis absorption spectra of HVO in the DI water solution (Figure S2c).…”
Section: Resultsmentioning
confidence: 99%
“…Peaks (001), (003), (004), and (005) (JCPDS #040-1296) expressing a particular direction of orientation are shown in Figure a. The V 2 O 5 · n H 2 O film retains the hydrate and layered phase on the ITO substrate, and the broadness of the peaks is attributed to the stronger crystalline indication . The water molecules’ presence in the HVO matrix was investigated by TGA (as shown in Figure b) using the A-Torrcca formula .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ravi et al introduced a straightforward one-step technique of synthesis a hydrate vanadium pentoxide (HVO) as HTL in OSCs . The solution-processed HVO phase have excellent hole transport properties.…”
Section: Classes Of Interlayer Materialsmentioning
confidence: 99%